Electrospun Tungsten‐Polyurethane Composite Nanofiber Mats for Medical Radiation‐Shielding Applications. Issue 2 (23rd November 2021) - Yun, Jaehan; Hou, Jian; Jang, Wongi; Kim, Sung‐Yul; Byun, Hongsik
Abstract: Electrospun composite nanofiber mats consisting of polyurethane (PU) and nontoxic tungsten powder are manufactured via electrospinning for use as X‐ray shielding materials. Upon systematical formation of tungsten‐PU composite nanofiber layers, heat and pressure are simultaneously treated to design light‐weight mats containing various amount of tungsten metals. After examining their structural and physical properties, the X‐ray mass attenuation coefficient, nitrogen permeability, and flexibility of the resulting mats are compared to conventional film‐type shielding mats. While the nanofiber‐based composite mats still exhibit a comparable X‐ray mass attenuation coefficient (9.64 cm 2 /g), their gas permeability (8.56 L/min) and flexibility (bending angle of 28.8°) are almost two and five times higher than those of conventional mats, respectively. This work clearly demonstrates the preparation of effective composite mats with controlled properties for the development of nontoxic shielding suits that can replace conventional lead‐based materials possessing environmental and health concerns. Abstract : An electrospinning strategy is utilized to manufacture composite mats consisting of nontoxic tungsten powder content up to 500 wt% and inexpensive polyurethane (PU) nanofibers for X‐ray shielding applications. The electrospun composite mats have shown comparable X‐ray mass attenuation coefficients compared to the conventional sheets prepared by a wet‐casting method, but their gas permeability and flexibility were almost two and five times higher than those of conventional mats, respectively.